Chemical Modifications for a Next Generation of Nucleic Acid Aptamers. (29th April 2022) - Chan, Kwing Yeung; Kinghorn, Andrew Brian; Hollenstein, Marcel; Tanner, Julian Alexander
Abstract: In the past three decades, in vitro systematic evolution of ligands by exponential enrichment (SELEX) has yielded many aptamers for translational applications in both research and clinical settings. Despite their promise as an alternative to antibodies, the low success rate of SELEX (∼30 %) has been a major bottleneck that hampers the further development of aptamers. One hurdle is the lack of chemical diversity in nucleic acids. To address this, the aptamer chemical repertoire has been extended by introducing exotic chemical groups, which provide novel binding functionalities. This review will focus on how modified aptamers can be selected and evolved, with illustration of some successful examples. In particular, unique chemistries are exemplified. Various strategies of incorporating modified building blocks into the standard SELEX protocol are highlighted, with a comparison of the differences between pre‐SELEX and post‐SELEX modifications. Nucleic acid aptamers with extended functionality evolved from non‐natural chemistries will open up new vistas for function and application of nucleic acids. Abstract : Cubane aptamer (cubamer) is a chemically modified nucleic acid aptamer incorporating cubane moieties into the nucleotide bases. The Figure shows a cubamer in complex with the malaria biomarker Plasmodium vivax lactate dehydrogenase (PvLDH), with high specificity relative to Plasmodium falciparum lactate dehydrogenase (PfLDH). Such specificity has not been possible with conventional DNA aptamers. This example demonstrates the enhanced functionality of modified aptamers. Herein, we review the chemistry, synthesis, selection, and application of such modified aptamers.